2008
DOI: 10.1111/j.1365-2338.2008.01193.x
|View full text |Cite
|
Sign up to set email alerts
|

Different methods of monitoring susceptibility of oilseed rape beetles to insecticides

Abstract: The resistance of oilseed rape pollen beetles to lambda‐cyhalothrin has increased in Germany over the period 2002 to 2007. Oilseed rape pollen beetles are very good at dispersing, therefore field results should always be compared with those of laboratory experiments. The response of oilseed rape pollen beetles to active substances may not be the same as that to formulated products. Bioassays in which beetles are exposed to insecticides on either complete inflorescences or flower buds give different results. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
29
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 6 publications
(10 reference statements)
2
29
0
5
Order By: Relevance
“…The development of this species is closely related to oilseed rape even though its adults also feed on different plant species (Charpentier 1985). Thieme et al (2008) Marczali and Keszthelyi (2003) monitored Meligethes species in oilseed rape with similar results. In relation to pollen beetle resistance to pyrethroids Derron et al (2004) reported M. viridescens is not resistant and was present in variable frequencies depending on the time and place where the samples were collected.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…The development of this species is closely related to oilseed rape even though its adults also feed on different plant species (Charpentier 1985). Thieme et al (2008) Marczali and Keszthelyi (2003) monitored Meligethes species in oilseed rape with similar results. In relation to pollen beetle resistance to pyrethroids Derron et al (2004) reported M. viridescens is not resistant and was present in variable frequencies depending on the time and place where the samples were collected.…”
mentioning
confidence: 66%
“…The importance of M. aeneus for oil seed rape in the Czech Republic is quite similar as it is in Germany (Glattkowski et al 2008) and Poland (Wegorek & Zamojska 2008). Not only one but usually more species of the genus Meligethes have occurred in winter oilseed rape crops (Thieme et al 2008). Agricultural practice does not distinguish among the individual species which are more or less abundant and often intermittently present in oilseed rape fields in Europe (Cook & Denholm 2008;Richardson 2008;Thieme et al 2008;Tóth et al 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations